Business Unit Development Management In improving Independence of Educational Institutions - Ernawati Kristinningrum; Renny Oktafia; Nurdyansyah Nurdyansyah (Proceedings of The ICECRS, 2020)
The most fundamental problem in education in Indonesia is the quality that has not exceeded the desired standards, including education staff, facilities, funding, management, processes and student achievement. Referring to the citation of the problem of financing which comes from the diversity of the current state of educational institutions, it raises the idea that it is very easy to build an organization that is based on profit or non-profit, but in the process, an organization should have to survive in the face of its environmental conditions. If you are able to adapt to the environment, so that the organization will survive, otherwise if not, ultimately only a name. Of course it's very easy to solve this problem. Another problem is the lack of funds, this problem is a fundamental reason that impedes the goals of an organization. The need for preventive measures in the procurement of funds is to build business units that generate profits for the establishment of an independent institution. The research in this article was conducted at Islamic education institutions, especially at Muhammadiyah 2 Sidoarjo High School, which aims to have educational institutions that have the right management in managing their business units, so that they receive income that can support the independence of educational institutions. The Business Unit to be investigated is specialized in leasing several business units owned by the Muhammadiyah 2 Sidoarjo High School. In this article, research conducted using a qualitative approach, the culminative approach is an approach that produces descriptive data in the form of written or oral words from people and observed behavior. The results of this study indicate that of the total business unit revenue only 17% is used for operational purposes, and 83% is left to the Sidoarjo SMAMDA educational institution. Thus it can be concluded that the entrepreneurship owned by Muhammadiyah 2 Sidoarjo High School in the form of several business units, with good management so as to provide income to the institution, this has helped Muhammadiyah High Schools to become independent educational institutions.